THE NON-INTERVENTION DOCTINE AND THE FOREIGN RELATIONS BETWEEN COSTA RICA AND NICARAGUA IN 1955 - Vanegas Avilés, Luz Marina (2014)
This paper analyze the different interpretations that can be a legal and political nature of the principle of non intervention, which allow time to consider joining all countries decide to do so and will even give their ratification; but when it comes to their application to specific cases, enforcement is uncertain or at least hesitant. Governments Continent hegemonic inclinations take advantage of the above procedure to carry out his purposes without suffering international condemnation justified, using the most varied pretexts to disguise their interference in the political affairs of weaker states. Costa Rica and Nicaragua in your history has taken interventionist attitudes sometimes, breach fundamental obligations of the Inter to achieve this is an analysis of the application of the Principle of Non-Intervention to relations between Costa Rica and Nicaragua in 1955.